Language Centers in the Age of Ubiquitous Technology and Eclectic Methodology - Sebastian, Paul (International journal of computer-assisted language learning and teaching, 2020)
This study was conducted in order to better understand how, if at all, language centers (LCs) are relevant in current technological and methodological contexts of second language education. Five language centers housed by four different institutions of higher education in the western United States were examined. Two representatives from each of the five centers were interviewed either in-person or over the phone (N = 10). Data was collected in the form of semi-structured interviews and on-site visits. The data was analyzed using a flexible combination of multi-level qualitative coding, descriptive statistics, and narrative analysis. This study confirms recent findings that have shown LCs to be a highly diverse group of institutions, particularly with respect to form and function. With respect to relevance, a common framework for discussing different language centers is outlined in the form of three paradigms: center/department, center/institution, and center/community.